2013
DOI: 10.1016/j.bjane.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Sedation-Analgesia in Elective Colonoscopy: Propofol-Fentanyl Versus Propofol-Alfentanil

Abstract: Fentanyl provides better operative conditions and reduces the need for additional propofol doses. These advantages cause a shorter recovery time. Therefore, propofol-fentanyl is superior to the propofol-alfentanil for sedation-analgesia in colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Further research on how symptomatic patients experience CCE and OC are needed and should include the clinical hospital setting with deep propofol sedation during OC. Screening individuals seem to have a high satisfaction with this [30], and also higher than individuals in moderate sedation [31], which our participants received during the OC.…”
Section: Discussionmentioning
confidence: 76%
“…Further research on how symptomatic patients experience CCE and OC are needed and should include the clinical hospital setting with deep propofol sedation during OC. Screening individuals seem to have a high satisfaction with this [30], and also higher than individuals in moderate sedation [31], which our participants received during the OC.…”
Section: Discussionmentioning
confidence: 76%
“…Recently ETCO 2 measuring has become a part of routine monitoring and capnographs are commonly used in operation theaters and intensive care units (7)(8)(9). Capnographic monitoring also prevents redundant blood gas analyses, thus reduces unnecessary costs (9).…”
Section: Discussionmentioning
confidence: 99%
“…Sedation is given in the endoscopy units for gastroscopy and colonoscopy procedures and patient's recovery is usually monitored with SpO 2 (8). ETCO 2 , which is the most important value in assessing ventilation, is not monitored routinely during sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, our data revealed less cognitive deterioration with propofol-alfentanil, which can be explained by the utilization of an opioid with a lower dose and shorter half-life. In a similar manner, Türk et al (35) compared propofol-fentanyl and propofol-alfentanil in 80 patients undergoing sedation during colonoscopy and found that propofol-fentanyl provides better operating conditions and shortens the recovery time and is thus more advantageous. The better recovery conditions provided by propofol-alfentanil in our study can be explained by the fact that propofol was used as an infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Bispectral index values and vital signs were recorded every minute for the first 10 min after induction of sedation and then at 15,20,25,30,35,40, and 45 min. Pain during the procedure was evaluated using the FPS (0-6), whereas pain after the procedure was evaluated using visual analogue scale (VAS) (0-10) at 5, 15, and 30 min after the procedure.…”
Section: Methodsmentioning
confidence: 99%